Does applying financial engineering methods have an impact on improving production efficiency? Does applying financial engineering methods have an impact on improving production efficiency? - Hameed, Ahmed Talib; Mohsin, Hayder Jerri; Bani Hani, Laith; Aldaaif, Hussien Atia (South Asian Journal of Social Sciences and Humanities, 2024)
The study aims to identify the application of financial engineering methods and production efficiency in the General Fertilizer Manufacturing Company in Basra. To obtain the required information, a sample of (250) workers working at various administrative and production levels in the company was selected as a study population.The questionnaire was used as a main tool for collecting data, and to test the study hypotheses: There is a significant effect of the processes of applying financial engineering methods in improving production efficiency. To measure the effect, analyze correlations, and then arrive at the research results, the two statistical programs (SMART PLS) were used. The research reached a number of conclusions, most notably the existence of an impact of the processes of applying financial engineering methods on the factors influencing the improvement of production efficiency. The study concluded with a number of recommendations, including the necessity of applying financial engineering methods in the company in the study population to improve production efficiency.